Silicone Models for Dermatological Education: Assessment of a New Teaching Tool by Dermatologists - Leonie Frommherz; Pascal Hering; Pia-Charlotte Stadler; Benjamin M. Clanner-Engelshofen; Markus Reinholz (Mattioli1885, 2023)
Introduction: The coronavirus pandemic forced universities to transfer academic curricula into the digital realm and calls for the introduction of new teaching methods to adequately compensate for the limited in-patient training. Especially in the field of dermatology, the use of 3D models presents an interesting opportunity to maintain the teaching of diagnostically essential sensory and haptic characteristics of primary lesions. Objectives: We developed a prototype silicone model and presented it to the medical service of the Department of Dermatology of the Ludwig-Maximilians University for evaluation. Methods: Silicone models demonstrating primary skin lesions were produced by using negative 3D-printed molds and different types of silicone. An online survey obtained evaluations from a group of dermatologists regarding the quality of previously supplied silicone 3D models and their potential use in medical education. Data from 58 dermatologists were collected and analyzed. Results: The majority of the participants rated the models overall as positive and innovative, providing constructive feedback for additional modifications, and recommended further implementation into the regular curriculum as an additional tool after the end of the pandemic. Conclusions: Our study underlined the possible advantages of using 3D models as a supplement in educational training even after the end of the SARS-CoV-2 pandemic.